2021
DOI: 10.1101/2021.08.04.21261618
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical characteristics and outcomes of COVID-19 breakthrough infections among vaccinated patients with systemic autoimmune rheumatic diseases

Abstract: Objective To describe the characteristics of COVID-19 vaccine breakthrough infections among systemic autoimmune rheumatic disease (SARD) patients. Methods We identified SARDs patients in a large healthcare system with COVID-19 vaccination at least 14 days prior to a positive SARS-CoV-2 molecular test. Details of the SARD diagnosis, vaccination status, and COVID-19 infection were extracted. Results Of 340 confirmed COVID-19 infections among SARDs patients between December 11th, 2020 (date of first COVID-19 vac… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…4 A recent report from the Mass General Brigham health care system identified COVID-19 infection in 340 patients with systemic autoimmune rheumatic diseases who were diagnosed after the availability of SARS-CoV-2 vaccines. 6 Breakthrough infection in fully vaccinated patients accounted for 16 infections (4.7%). Of these breakthrough infection cases, 15 (93%) were symptomatic, 6 (38%) were hospitalized, 1 (6%) required mechanical ventilation, and 2 (13%) died.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…4 A recent report from the Mass General Brigham health care system identified COVID-19 infection in 340 patients with systemic autoimmune rheumatic diseases who were diagnosed after the availability of SARS-CoV-2 vaccines. 6 Breakthrough infection in fully vaccinated patients accounted for 16 infections (4.7%). Of these breakthrough infection cases, 15 (93%) were symptomatic, 6 (38%) were hospitalized, 1 (6%) required mechanical ventilation, and 2 (13%) died.…”
mentioning
confidence: 99%
“…Of these breakthrough infection cases, 15 (93%) were symptomatic, 6 (38%) were hospitalized, 1 (6%) required mechanical ventilation, and 2 (13%) died. 6 In a recent study of hospitalized patients with a breakthrough infection, 44% were found to be vaccinated immunocompromised patients. 7 Findings from these studies suggest that blunted immune responses after SARS-CoV-2 vaccination in some patients with immune dysfunction may be associated with an increased risk for a breakthrough COVID-19 infection that can have severe and even fatal outcomes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While patients with IMIDs on BCDTs have been recognized to be vulnerable to severe COVID-19 infections, 3,4,6,7 relatively scant data exist regarding their risks for and outcomes of breakthrough infections 2,18 . The current cohort of breakthrough patients consisted of nearly equal numbers of patients with rheumatic and neuro-inflammatory disease and most (91.9%) were either fully vaccinated or boosted, with only 6 (8.1%) with incomplete vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…The deployment of vaccines to both prevent infection with SARS-CoV-2 as well as limit the severity of COVID-19 has proven efficacious for the general population. However, data on patients with underlying immunocompromising conditions, including those with immune mediated inflammatory diseases (IMIDs), suggest they have both an increased likelihood for developing breakthrough infections as well as for experiencing more severe outcomes despite full vaccination status 1,2 .…”
Section: Introductionmentioning
confidence: 99%